Orientações curriculares e proposição de expectativas de aprendizagem para o ciclo II de Matemática: contribuição para a formação continuada de professores de Matemática de uma escola da rede municipal da cidade de São Paulo, no período de 2005 a 2012 - Ishii, Antonella Bianchi Ferreira (2013)
This study focuses on the introduction of a prescribed curriculum in municipal schools in the city of São Paulo. As for the curriculum component, the choice was mathematics of the second stage of schooling (6th-9th grades). This investigation was guided by the following question: to what extent the Curriculum Guidelines and Proposition of Learning Expectations of Mathematics for 6th-9th grades contribute to the ongoing training of mathematics teachers? In order to answer this question I have chosen one high school in the municipal city of São Paulo as a field of research. This choice allowed me to examine the impacts of Curriculum Guidelines, the Proposition of Learning Expectations and also the introduction of other intermediary curriculum created with the aim to contribute to a full implementation of the learning expectations envisaged in the Curriculum of São Paulo. The research is based on a qualitative approach. Interviews were carried out with educators from the technical area of São Paulo municipality as well as with teachers who worked at the school researched and used the Curriculum Guidelines. This approach also allowed the constitution of a focus group with mathematics teachers from the said school, which allowed the identification of feelings and representations around the use of the document "Curriculum Guidelines and Propositions of Learning Expectations for Mathematics for 6th to 9th grades‖ The testimony of collaborators highlights the role of continuing education not only as a way of getting updated, but also as means of filling the gaps inherited from the initial training of most teachers of the municipal teaching network